EDUCATIONAL MODEL FOR CROSS-GENERATIONAL COLLABORATION (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
The paper's considerations relate to an Erasmus+ project called Generation: Smart. Social Competences Transmedia Bridge To Cultivate A New Culture For Cross-Generational Collaboration. The consortium agreed that due to profound changes in the contemporary Network Societies, people of various generations have to collaborate. However, it is a complex issue due to the divergent life purposes of different aged people. Thus, the project's targeted group, i.e., educators who support adult learners, should be equipped with an educational model that constitutes a solution to this situation. The assumption was that such a model is to include social competences enabling the processes of cross-generational collaboration. Information technology transmedia blend is supposed to bridge the gap between generations. In the paper, we present an overlook of the research that focuses on developing such a framework model. The research features triangulation, which means the analysis of both quantitative and qualitative data. It is structured in three parts. The first one deals with the statistical embracement of the social environment in which the cross-generational collaboration occurs in project partner countries. It is quantitative desk research that utilizes Eurostat information. It is worth pointing out that the research is in statu nascendi. In two consecutive parts, the researchers want to acknowledge the cross-generational collaboration in working life and everyday life. Here, the survey method and the questionnaire interview technique serve as the qualitative research method. Two research groups are to be reached: entrepreneurs and the Third Age Universities' participants. The results of the above two stages will be known after the publication of this paper. Nonetheless, a proto-model recommendation is presented along with educational conclusions on how to use the model. The concept is based on the prior partners' analysis and design work.